Air Pollution and Adult Cognition: Evidence from Brain Training - Andrea La Nauze; Edson R. Severnini (Institute of Labor Economics (IZA), 2021)
We exploit novel data from brain-training games to examine the impacts of air pollution on a comprehensive set of cognitive skills of adults. We find that exposure to particulate matter (PM2.5) impairs adult cognitive function, and that these effects are largest for those in prime working age. These results confirm a hypothesized mechanism for the impacts of air pollution on productivity. We also find that the cognitive effects are largest for new tasks and for those with low ability, suggesting that air pollution increases inequality in workforce productivity.
Keywords: Q53; J24; I14; I24; 330; air pollution; particulate matter; cognition; cognitive skills